2006
DOI: 10.1007/s00442-006-0368-5
|View full text |Cite
|
Sign up to set email alerts
|

Short dry spells in the wet season increase mortality of tropical pioneer seedlings

Abstract: Variation in plant species performance in response to water availability offers a potential axis for temporal and spatial habitat partitioning and may therefore affect community composition in tropical forests. We hypothesized that short dry spells during the wet season are a significant source of mortality for the newly emerging seedlings of pioneer species that recruit in treefall gaps in tropical forests. An analysis of a 49-year rainfall record for three forests across a rainfall gradient in central Panama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
107
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(115 citation statements)
references
References 49 publications
6
107
0
2
Order By: Relevance
“…However, the important point is that both the experimental observations and our modelling indicate that bare soil in a large gap can experience sufficient drying to kill shallow rooted seedlings. This was confirmed by Engelbrecht et al (2006) who observed up to 20% mortality of 3.5-month-old seedlings of pioneer species after 4 days of rainfall exclusion, rising to up to 40% after 11 days, in comparison to a control treatment.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…However, the important point is that both the experimental observations and our modelling indicate that bare soil in a large gap can experience sufficient drying to kill shallow rooted seedlings. This was confirmed by Engelbrecht et al (2006) who observed up to 20% mortality of 3.5-month-old seedlings of pioneer species after 4 days of rainfall exclusion, rising to up to 40% after 11 days, in comparison to a control treatment.…”
Section: Discussionsupporting
confidence: 60%
“…This is mainly because in the dry-season, the soil is much drier at depth so that the zone wetted by rainfall dries both by evapotranspiration and downward movement, whereas during the wet-season capillary recharge slows the rate of surface drying. Engelbrecht et al (2006) observed 4Q Springer the drying of bare soil in large gaps during the middle of the wet-season on the Barro Colorado Nature Monument adjacent to BCI. After only 4 days of rainfall exclusion by a plastic roof, the matric potential of soil from a depth of 5-10 mm had fallen to -4.5 MPa.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…However this comes at the cost of an increased transpirational water loss from the leaf. Especially in dry forests, where evaporative demand is greater than in moist forests and the dry season forms a bottleneck for survival of juvenile trees (Engelbrecht et al 2006), pioneer species will be filtered out of the landscape and persist in relatively wet habitats. In a recent study we addressed such hydraulic habitat partitioning among 40 different dry-forest tree species and our findings suggested that, similar to S. riparium, other pioneer species also had greater moisture requirements, and were thus less drought-tolerant, than shade-tolerant species (Markesteijn 2010).…”
Section: Seasonal Changes In Plant Water Statusmentioning
confidence: 99%
“…Water availability in these ecosystems affects the germination patterns (Garwood,983) and is considered one of the most important factors in modifying the structure and dynamics of this community (Murphy and Lugo,986). In a tropical dry forest, the soil water potential in the dry season can achieve up to -.5 MPa (Engelbrecht et al, 2006). The majority of species produces and disperses seeds in the dry season before reliable rains begin, which then allows them to germinate when the soil humidity is optimal (Baskin and Baskin, 998;Ceccon et al, 2006).…”
mentioning
confidence: 99%